Elevated PD-1 expression and decreased telomerase activity in memory T cells of patients with symptomatic Herpes Zoster infection - Zangeneh, Z.; Golmoghaddam, H.; Emad, M.; Erfani, N.; Doroudchi, M. (Cellular and Molecular Biology, 2014)
We investigated PD-1 levels on VZV-specific CD8+ T-cells of patients with zoster and the effect of PD-1 on the telomerase activity. CD3, CD8, CD137 and PD-1 expressions were analyzed on PBMCs from 9 symptomatic and 5 asymptomatic individuals. The effect of PD-1 blockade at the time of stimulation on the telomerase activity of non-senescent CD57-CD45RO+CD8+CD3+ memory T-cells was evaluated. PD-1 was elevated on CD8+ T-cells in patients. The frequency of PD-1+ and CD137- cells in total CD3+CD8+ T cells of patients was elevated compared to controls. Telomerase activity of non-senescent memory T-cells was lower than that of controls. Blockade of PD-1 at the time of stimulation increased telomerase activity of non-senescent memory T-cells, accompanied by increased CD137 expression. Low telomerase activity of the patients with reactivated zoster could be partially overcome by blocking PD-1 pathway.